Bioengineering in women's health, volume 2: pregnancy—from implantation to parturition. Issue 5 (16th August 2019) - Miller, Kristin S.; Myers, Kristin; Oyen, Michelle
Abstract : This special issue of Interface Focus is the second of two sets of articles on the topic of bioengineering in women's health. This second issue in the series focuses on pregnancy, a dynamic time in a women's life that involves dramatic physiologic changes within a relatively small timeframe. Pregnancy demands endurance and resilience of one's body and represents a critical component of women's health research. The health of an individual leading up to, during and after pregnancy is paramount for reproductive health and the lifelong health of offspring. The articles in this issue explore physiological events that support reproduction spanning from embryo implantation, through gestation, to delivery and parturition. Specifically, the articles highlight essential developments in placenta, fetal membranes, cervix, pelvic floor and anthropometry research. The featured bioengineering disciplines deployed to study such complex biological processes are diverse, with articles detailing the latest advancements in computational modelling at various biological length-scales, biomaterial design, material modelling, non-invasive diagnostic techniques, microfluidic devices and experimental mechanics. This second issue continues the first in this series, on the physiology of the non-pregnant woman.